2021
DOI: 10.1155/2021/5623601
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Risk Factors for Prognosis of Cirrhotic Patients with Hepatic Encephalopathy

Abstract: Background and Aims. Hepatic encephalopathy (HE) is characterized by recurrence and poor quality of life. Acute-on-chronic liver failure (ACLF) mainly occurs in patients with chronic liver diseases and often presents with HE. Several predictive models have been proposed to predict the outcomes of these patients. Our study is aimed at identifying associated risk factors and the prognostic accuracies of predictive models in HE patients with or without ACLF. Methods. Patients with liver cirrhosis were retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…Although its p value was not small enough to allow us to claim statistical significance (p value = 0.055), the degree of association with an OR of 2.24 made it worth commenting on. In addition, its clinical importance was supported by findings from various studies [ 36 38 ]. Further study with a larger sample size may be needed.…”
Section: Discussionmentioning
confidence: 79%
“…Although its p value was not small enough to allow us to claim statistical significance (p value = 0.055), the degree of association with an OR of 2.24 made it worth commenting on. In addition, its clinical importance was supported by findings from various studies [ 36 38 ]. Further study with a larger sample size may be needed.…”
Section: Discussionmentioning
confidence: 79%
“…Endoscopic therapy is effective in controlling AVB especially in Child-Pugh class C cirrhotic patients while early TIPS has not been con rmed the effect on survival of these patients [21,22]. Child-Pugh was superior to the other factors in HE patients for prediction of in-hospital mortality [23,24], and also an important risk factors for predicting postoperative mortality in cirrhotic patients [25]. Five death cases in present study were all Child-Pugh class C, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 93%
“…Second, high serum levels of INR and TBIL generally indicate coagulation failure and liver failure, respectively. Many prognostic studies have reported that the abovementioned parameters are indicators of survival in patients with liver diseases [ 22 , 23 ]. Furthermore, the parameters are widely used in prognostic scores for patients with ACLF [ 14 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%